Tourism Development Through the Global Hub Bandar Kayangan in Lom-bok Utara (KLU) District - Suriadi, Irwan; Sutanto, Himawan; Dakwah, M. Mujahid (Future Science / FSH-PH Publications, 2023)
The Problem in this research is: (a) How is the development of the Bandar Kayangan Global Hub supporting tourism in KLU, (b) How does the Bandar Kayangan Global Hub development policy model support tourism in KLU.The data used in this study are primary data that comes from tourism stakeholders and secondary data that comes from the KLU Tourism Office and the KLU Central Statistics Agency (BPS). The analytical method used in this research is SWOT analysis (strength, weakness, opportunity, and threat). The results showed that the internal strategy factor (strength) with the highest score of 0.28, meaning that the Bandar Kayangan Global Hub in KLU must have a commitment from the community to develop its area to improve the standard of living of its people so that it is more advanced, such as by increasing people's income levels. The internal strategy factor (weakness) with the highest score of 0.13 means that the Bandar Kayangan Global Hub in North Lombok Regency must carry out quite intensive socialization and promotion through various media. The external strategy factor (opportunity) with the highest score of 0.22, meaning that the Global Hub at Bandar Kayangan in KLU can develop well because it has opportunities for community empowerment around Bandar Kayangan. The external strategy factor (threat) with the highest score of 0.21, meaning that the Bandar Kayangan Global Hub in KLU is still hampered by its development because the regional economy in particular and the national economy in general are still affected by the Corona COVID-19 pandemic.